Description Of Posture Mother Knowledge About Treatment Of Perineum In The Conference - Marwidah; Rusnawati (Jurnal Life Birth, 2017)
The puerperium is the period that begins after the birth of the placenta and ends when the uterine uterus returns to its state before pregnancy, the puerperium for about 6 weeks (Astutik, 2015). Lack of knowledge of how to treat perineal wounds will lead to infections, complications, and the death of postpartum mothers. The purpose of this study was to determine the knowledge description of Postpartum mothers about Perineum Wound Care during the puerperium at Lembanna Public Health Center, Kajang Sub-district, Bulukumba Regency in 2017. This study used a descriptive study and was carried out at the Lembanna Health Center, Kajang Sub-district, Bulukumba District in June 2017 with a sample of 30 respondents of Postpartum mothers who used a sampling technique, namely Total Sampling. The research instrument is a closed questionnaire. From the research that has been done, it is obtained that from 30 respondents, those who have a good category of knowledge are 10 respondents (33.3%), who have enough knowledge with categories of 8 respondents (26.7%) and those who have knowledge in the poor category as many as 12 respondents (40.0%). It can be concluded that the description of Postpartum Mother Knowledge about Perineal Wound Care during the Postpartum Period in the working area of ​​Lembanna Health Center, Kajang District, Bulukumba Regency 2017. Of the 30 respondents in general who were well knowledgeable (33.3%), sufficient (26.7%), less (40.0%).